Using Visual Arts Education and Reflective Practice to Increase Empathy and Perspective Taking in Medical Students - Sina Rezaei; Andrew Childress; Bhavika Kaul; Kelly Magill Rosales; Alana Newell; Stacey Rose (Association of American Medical Colleges, 2023)
Introduction Empathy is a critical competency for health care providers. However, empathy levels in medical students and residents have been shown to paradoxically decrease during training. Arts and humanities education and reflective practice may reduce burnout and promote empathy during medical school. Methods We developed and implemented an art education elective for medical students focusing on observation and reflective practice and measured its impact on empathy. Between 2017 and 2022, first-year medical students were offered an annual, 4-week elective led by art educators that featured visualization exercises and discussions on the role of bias and perspective in art interpretation. Curriculum effectiveness and impact on empathy were measured using the validated Interpersonal Reactivity Index (IRI) and self-assessments. Results One hundred twenty-eight students participated in the elective over a 5-year period; 89 (70%) completed assessments. Students reported improvements in empathic communication, recognition of bias, and observation skills. IRI data demonstrated a significant increase in perspective taking (19.0 vs. 20.2; p < .0125). Discussion Participation in the elective was associated with self-reported improvements in visual observation, awareness of bias, and empathetic communication. IRI results showed that participants also demonstrated improved perspective taking. Since perspective taking is a cognitive component of empathy, we have provided some empirical evidence that arts education in medical school can promote empathic attitudes and skills.